Pengaruh asap berbagai jenis rokok terhadap peroksidasi lipid plasma tikus putih (rattus norvegicus,l) = The Effect of Smoke from Several Kind of Cigarettes on White Rat's (Rattus norvegicus,L) Plasma Lipia Per oxidation - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Good body health is influenced by many factors, such as nutrition, environment, habits, and a balance between the presence of free radicals and antioxidant system in the body. Habits could damage health for example smoking. In vitro studies showed that smoked could damage the balancing between free radicals and antioxidant system, so that it could cause oxida-tive damage of the tissues. Oxidative damage of tissues among others could be reflected by lipid peroxidation. Controversy from results of in vivo experiments was still encountered. There were many kinds of cigarette in the market, such as kretek, mild, filter and non-filter cigarettes. The aim of this experiments were to prove that cigarette's smoke which was used to expose test animals could influence plasma lipid peroxidation